Cover Picture: Macromol. Theory Simul. 2∕2015. Issue 2 (February 2015) - Hebbeker, Pascal; Plamper, Felix A.; Schneider, Stefanie
Abstract : Back Cover: Star polymers with arms of two different homopolymers with a weak mutual attraction are investigated using Monte Carlo simulations, and the effect of the polymer architecture on the complexation behavior of the polymers is studied. The star architecture promotes an internal complexation, which is indicated by a reduction of the end‐to‐end distance of the polymer chains. Further details can be found in the article by Pascal Hebbeker, Felix A. Plamper, and Stefanie Schneider*on page 110 .